IDEAS TO ENHANCE ENGLISH LEARNERS’ MOTIVATION THROUGH TECHNOLOGY BASED TEACHING MEDIA - Emmi Naja (Pusat Pengembangan Bahasa IAIN Tulungagung, 2014)
We see and face that our students not really motivated when they learn English, feeling bored and not interesting to English. Teaching media usage can face this problem, because the use of teaching media can attract students’ attention to the subject. However, even the teacher used teaching media to explain materials, sometimes it is not a good way to avoid students’ boredom, because they not really interesting to teaching media used. This article tries to give some ideas related to the problem above, by offering ideas about interesting teaching media that is technology based teaching media. This issues based on the fact that the growth of technology today is very massive, and students are very familiar and interested in technology. So, it is hoped as an English teacher to adapt students’ interest in term of technology as teaching media.